2020
DOI: 10.1038/s41536-020-00103-1
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps promote scar formation in post-epidural fibrosis

Abstract: Low back pain following spine surgery is a major complication due to excessive epidural fibrosis, which compresses the lumbar nerve. The mechanisms of epidural fibrosis remain largely elusive. In the drainage samples from patients after spine operation, neutrophil extracellular traps (NETs) and NETs inducer high-mobility group box 1 were significantly increased. In a mouse model of laminectomy, NETs developed in the wound area post epidural operation, accompanied with macrophage infiltration. In vitro, macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
(51 reference statements)
4
14
0
Order By: Relevance
“…We also observed that living microglia and neutrophils increase their ET formation following durotomy. This result correlates with other studies demonstrating the formation of NETs by infiltrating neutrophils in mouse models of durotomy (Jin et al, 2020). However, this is the first report of MiET formation in the spinal cord following durotomy.…”
Section: Discussionsupporting
confidence: 92%
“…We also observed that living microglia and neutrophils increase their ET formation following durotomy. This result correlates with other studies demonstrating the formation of NETs by infiltrating neutrophils in mouse models of durotomy (Jin et al, 2020). However, this is the first report of MiET formation in the spinal cord following durotomy.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have demonstrated that NETs are implicated in atherosclerosis, fibrosis and thrombotic CVD (18)(19)(20). Thus, we first used ELISA to measure the levels of MPO/DNA complexes and citrullinated histone H3 (CitH3), well-defined circulating markers of NET release (14), in the plasma of EH treatment-naïve (untreated) patients.…”
Section: Increased Levels Of Circulating Nets In Untreated Newly-diagnosed Eh Patientsmentioning
confidence: 99%
“…NETs stimulated by free fatty acids may influence monocyte-derived macrophage infiltration and inflammation in the liver [ 39 ]. In the animal model of post-epidural fibrosis, NETs were found to increase the production of extracellular matrix components in macrophages [ 40 ]. In a systemic vasculitis known as deficiency of ADA2, NETs induced production of inflammatory cytokines from macrophages through NF-κB nuclear translocation in macrophages [ 41 ].…”
Section: Discussionmentioning
confidence: 99%